(untitled) (Castilla. Estudios de Literatura, 2020)
The objective of this article is to identify the archive on which six contemporary Latin American novels are based, in order to analyze the discourses from which they are built, and which also take part in reality. In this way, based on the underlying discourses that participate in and outside literature, we propose the triad archive-novel-reality as a form of interpretation of the Latin American present. To that effect, based on the theory postulated by González Echevarría in Myth and Archive (1990), we formed a corpus of Latin American novels published in the 21st century whose writing is based on a previous speech, recorded on an archive. We postulate the hypothesis that González Echevarría’s theory is productive not only to explain the Latin American novel analyzed in his study, but the one that was yet to come: that of the present century.